How School Climate Affects Teachers' Individual Innovativeness: The Mediating Role of Teacher Autonomy - Ozdemir, Tuncay Yavuz; Cakalci, Neslihan (Universitepark, 2022)
Background/purpose – The continuity of society is ensured through schools where educational activities are formally conducted. There exists a wide range of tasks that are assigned to educational systems and schools, and three concepts play a critical role for the successful completion of those tasks: school climate, individual innovativeness, and teacher autonomy. The aim of this study was to investigate whether teacher autonomy had a mediating role in the relationship between school climate and teachers' individual innovativeness. Materials/methods – The relational survey model was used in the study, with 617 elementary school teachers selected using simple random sampling. Data were collected using three scales: the School climate scale, the Teacher autonomy scale, and the Individual innovativeness scale. The collected data were analyzed using regression and correlation analyses. In addition, Bootstrap analysis was performed through IBM SPSS v.24.0 (Hayes, 2013) with PROCESS Macro 3 and “Simple Mediation Model 4” used to examine the significance of the mediation effect. Results – The findings revealed that a positive, moderate, and significant relationship exists between school climate, individual innovativeness, and teacher autonomy. Bootstrap analysis showed that teacher autonomy had a significant mediating effect in the relationship between school climate and individual innovativeness. Furthermore, the Sobel test proved the significant mediating effect of teacher autonomy since the Z value was at the desired level. Conclusion – It was found that teacher autonomy had a mediating role in the relationship between school climate and teacher innovativeness. Since this is the first study to examine the mediation effect of teacher autonomy on the relationship between teacher innovativeness and school climate, further research is needed with different samples to verify the findings. © 2022 by the author(s).
Keywords: education; individual innovation; mediator variable; School climate; teacher autonomy; training